An An Analysis of Economic Differences and Service Quality on Patient Satisfaction: A Case Study of BPJS and Non-BPJS Patients at Tawangmangu Public Health - Agustin Dian Pertiwi; Susilaningtyas Budiana Kurniawati; Supartini Supartini (Universitas Veteran Bangun Nusantara Sukoharjo, 2025)
This study aims to analyze the differences in patient satisfaction levels among BPJS PBI, BPJS Non-PBI, and Non-BPJS groups, as well as to examine the influence of economic factors and service quality on patient satisfaction at the Tawangmangu Public Health Center. This research employs a quantitative approach, using data collection techniques through questionnaires distributed to 130 respondents selected via purposive sampling based on specific criteria. The results show that economic factors have a significant effect on patient satisfaction. Additionally, all dimensions of service quality (reliability, responsiveness, assurance, tangible evidence, and empathy) also significantly influence patient satisfaction. ANOVA analysis reveals a significant difference in satisfaction levels among the patient groups, with BPJS PBI and BPJS Non-PBI patients reporting higher satisfaction levels compared to Non-BPJS patients.